Etymological trends in the Sanskrit vocabulary - Hellwig, Oliver (LLC, 2010)
The article examines how the etymological composition of the Sanskrit lexicon is influenced by time and whether this composition can be used to date Sanskrit texts automatically. For this purpose, statistical tests are applied to a corpus of lexically analyzed texts. Results reported in the article may contribute to the diachronic lexicography of Sanskrit and help to develop computational methods for analyzing anonymous and undated Sanskrit texts.